A Child with a Rare Extraosseous Extension and Pathologic Fracture from a Vertebral Hemangioma: A Case Report. Issue 4 (October 2017) - Gajaseni, Pawin; Labianca, Luca; Lacerda, Iara; Weinstein, Stuart
Abstract : Case: We present a case of a pathologic vertebral fracture and encroachment into the spinal canal from a vertebral hemangioma in a 13-year-old boy. The original approach of embolization followed by an anterior-posterior resection and stabilization through a costotransversectomy had to be converted intraoperatively to a combined anterior and posterior approach secondary to excessive bleeding. Conclusion: Because of the hypervascularity and the extensive nature of aggressive vertebral hemangiomas, surgeons attempting procedures similar to the case described herein must be prepared to adapt to the circumstances when preoperative embolization is not totally effective. Surgical technique, proper anesthesia, and patient clotting capacity are important factors to consider.